2021
DOI: 10.7759/cureus.13175
|View full text |Cite
|
Sign up to set email alerts
|

Hyponatremia and Its Correlation With Hepatic Encephalopathy and Severity of Liver Disease

Abstract: Background and objective Hepatic cirrhosis is one of the leading causes of morbidity and mortality worldwide. Patients with cirrhosis frequently develop complications such as ascites, variceal bleeding, and hepatic encephalopathy (HE). The clinical manifestations of HE range from the mildly altered level of sensorium to severely altered consciousness levels, difficulty in judgment, the day-night reversal of sleep, flapping tremor of hands, and irrelevant talking or speech. Patients with hyponatremia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
2
4
1
Order By: Relevance
“…Furthermore, in 96 patients with hyponatremia, 25.0% had mild hyponatremia, 58.3% moderate while remaining 16.7% had severe hyponatremia. 21 Our findings are very consistent with what Younas A et al reported where significant correlation of severity of hyponatremia was observed with regards to grades of HE (p<0.001). 21 Our findings are consistent with the published literature that hyponatremia is a common finding especially in patients presenting with HE.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, in 96 patients with hyponatremia, 25.0% had mild hyponatremia, 58.3% moderate while remaining 16.7% had severe hyponatremia. 21 Our findings are very consistent with what Younas A et al reported where significant correlation of severity of hyponatremia was observed with regards to grades of HE (p<0.001). 21 Our findings are consistent with the published literature that hyponatremia is a common finding especially in patients presenting with HE.…”
Section: Discussionsupporting
confidence: 93%
“…21 Our findings are very consistent with what Younas A et al reported where significant correlation of severity of hyponatremia was observed with regards to grades of HE (p<0.001). 21 Our findings are consistent with the published literature that hyponatremia is a common finding especially in patients presenting with HE. Researchers in the past have shown that patients of liver cirrhosis with hyponatremia have higher rates of adverse inhospital outcomes.…”
Section: Discussionsupporting
confidence: 93%
“…Younas A, et al conducted a study in liver disease patients with hyponatremia, which showed serum sodium levels ranging from 115 to 127meq/L (mean 121.41±5.17meq/L). 15 Low serum sodium levels was present among these patients in 96 (36.9%) patients which was lower that what our study had showed. Fiftyone (53.12%) patients among these were male and 45 (46.8%) were female.…”
Section: Discussioncontrasting
confidence: 77%
“…Most of the patients (90%) recover from the acute infection by forming neutralizing antibodies, and the rest of the patients develop chronic hepatitis B [ 1 ]. Similarly, HCV infection also manifests as both acute and chronic hepatitis C. Most cases develop a chronic infection that leads to cirrhosis, hepatocellular carcinoma, cardiovascular disorders, and neurological manifestation like hepatic encephalopathy [ 12 , 13 ]. Moreover, hemodialysis patients suffer from anxiety and depression, which can be exacerbated by this infection, leading to increased morbidity and mortality [ 14 ].…”
Section: Discussionmentioning
confidence: 99%